Behavioral rationality as a foundation for public policy studies. (June 2017) - Jones, Bryan D.
Abstract: Cognitive processing applies to a single human being, yet most key social processes are organized in collectives, and connecting them is not a simple task. I review the basic ways in which social and behavioral scientists have tried to link the individual with the system, illustrating the progress that has been made in this endeavor. We are closer than we ever have been to producing a behavioral model that integrates cognitive science yet does not produce a confusing overabundance of findings that have systems level implications. I conclude that we may well be at a tuning point in which the fully rational model of human choice, currently used as the microfoundation for economics and the study of political institutions, is replaced by a more robust behavioral model of choice that relies on developments in the cognitive sciences.